Optimizing shared decision making in older adults with basal cell carcinoma: experiences from a specialized outpatient clinic. (27th December 2021) - van Winden, M.E.C.; Klösters, F.M.; Hamaker, M.; Olde Rikkert, M.G.; van de Kerkhof, P.C.M.; de Jong, E.M.G.J.; Lubeek, S.F.K.
Abstract :